Sistem Penghitung Jumlah Pengunjung Ruangan Secara Otomatis - Iqbal May Aryanto; Syaiful Mansur; Ayu Sintianingrum (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Increasing population growth will affect the mobility of people in carrying out various activities in certain places. Therefore it is necessary to control the number of visitors visiting certain locations/places. The purpose of this research is to build an automatic system to be able to calculate the number of visitors to the room automatically. The research method used is experimental by utilizing Arduino uno and using an ultrasonic sensor, in this case the ultrasonic sensor will be used to be able to detect every movement of a person or human that passes through the sensor. So that it is hoped that the tool built can work optimally in detecting the number of people or visitors who will enter the room or building. The results of this study are the design of a system for calculating the number of visitors in a room or building that has high mobility. The device built uses an ATmega328 microcontroller and an ultrasonic sensor as a human detector. The configuration process for several devices used is using the Arduino IDE software. The conclusion that can be drawn in this study is that the results of testing the performance of the tool show that it is able to provide convenience to building or room managers in knowing the number of visitors entering, leaving visitors and visitors who are still in the room or building.